2021
DOI: 10.3389/fnut.2021.661056
|View full text |Cite
|
Sign up to set email alerts
|

Future Land Use for Insect Meat Production Among Countries: A Global Classification

Abstract: A potentially suitable alternative to reduce land use by livestock production is insect meat production. However, land use predictions for insect meat production, which are important in the planning of food production strategies in each country, have not been well-performed. To consider the strategy of insect meat production with regard to land use, the categorical perspectives of countries would be highly useful. Here, using previous simulation results, we used random forest machine learning to classify the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Thus, insect farming can potentially reduce land use, increase food production, and improve environmental sustainability (Doi & Mulia, 2021; van Huis & Oonincx, 2017). Insect farming typically involves breeding insects in a controlled environment, such as a greenhouse or indoor facility, where temperature, humidity, and lighting can be carefully controlled to optimize growth and reproduction.…”
Section: Insects Farmingmentioning
confidence: 99%
“…Thus, insect farming can potentially reduce land use, increase food production, and improve environmental sustainability (Doi & Mulia, 2021; van Huis & Oonincx, 2017). Insect farming typically involves breeding insects in a controlled environment, such as a greenhouse or indoor facility, where temperature, humidity, and lighting can be carefully controlled to optimize growth and reproduction.…”
Section: Insects Farmingmentioning
confidence: 99%
“…It is important to consider that circular and soilless alternatives, such as insect farming or food waste for feed, may also have unintended impacts on land-use change especially as the scale and size of production systems increase (Shah and Wu, 2019;Doi and Mulia, 2021). Soilless systems require a robust management plan to avoid the abandonment of crop land, which in combination with effects of climate change in the South, including increasing temperatures and frequencies of extreme droughts, can exert pressures on soil organic carbon and biodiversity (Pacheco et al, 2018;Olsson et al, 2019;Winkler et al, 2021).…”
Section: Environmentalmentioning
confidence: 99%
“…Saprophagous insects such as H. illucens and M. domestica satisfy their water demand directly via the input substrate, so proteins produced by insets feeding on side-streams have a much lower water footprint even compared to plant proteins (Joly and Nikiema, 2019;Rumpold and Schlüter, 2013). Furthermore, insect farming does not need a large area of land (Doi and Mulia, 2021). Life-cycle assessments for H. illucens (Salomone et al, 2017) and M. domestica (Van Zanten et al, 2015) revealed land requirements of 0.05 and 0.032 m 2 /yr/kg protein, respectively, compared to almost 9 m 2 /yr/kg protein for soybean (Salomone et al, 2017).…”
Section: Sustainability Of Insect Proteinmentioning
confidence: 99%